Suicide mortality risk in a cohort of individuals treated for alcohol, heroin or cocaine abuse: Results of a follow-up study. (February 2021) - Pavarin, Raimondo Maria; Sanchini, Samantha; Tadonio, Leonardo; Domenicali, Marco; Caputo, Fabio; Pacetti, Monica
Highlights: Substance and alcohol use disorders are associated with significant risk of suicide mortality The aim of this study was to examine suicide mortality risk in a cohort of individuals who turned to a public treatment centre for addiction for primary abuse of alcohol, heroin or cocaine We highlights an increase in suicide mortality during the economic recession, and in the year of first contact with the treatment service Further studies are needed in order to better understand the relationship between completed suicide and mental health problems among patients with SUDs and AUDs. Abstract: Cohort study. This follow-up study (from 1975 to 2016) was aimed to estimate the mortality risk for suicide in a cohort of patients presenting to a public treatment centre for addiction (SERD) with Alcohol Use Disorder (AUD), Heroin Use Disorder - HUD or Cocaine Use Disorder (CUD), also relating to their access to a Mental Heath Service. Crude Mortality Rates for suicide were higher for patients with AUDs, for men and subjects 45–64 years old. Hanging was the main cause of suicide death. We highlight an increase in mortality in the period 2009–2012, which coincides with the economic recession, and in the year of first contact with a SERD. The Standardized Mortality Ratios (SMRs) were 4.9, higher among females than males. From the multivariate analysis, a higher risk for patients that were separated or divorced was observed. The results of our study provide some guidance on the features of subjects at greatest risk of death from suicide, which may be useful in reducing and preventing suicide and gaining a better clinical management of patients with SUDs.